PROGRAMMING ML.NET. - ESPOSITO, DINO (MICROSOFT, 2021)
With .NET 5s ML.NET and Programming ML.NET, any Microsoft .NET developer can solve serious machine learning problems, increasing their value and competitiveness in some of todays fastest-growing areas of software development. World-renowned Microsoft development expert Dino Esposito covers everything you need to know about ML.NET, the machine learning pipeline, and real-world machine learning solutions development. Modeled on his popular Programming ASP.NET books, this guide takes the same scenario-based approach Microsofts team used to build the ML.NET framework itself. Esposito presents and illuminates ML.NETs dedicated mini-frameworks (ML Tasks) for specific classes of problems, and draws on personal experience to help developers apply these in the real world, where a problems complexity can vary widely based on data availability or the specific results you need. In a full section on ML.NET neural networks, Esposito introduces key concepts and presents realistic examples you can reuse in your own applications. Along the way, Esposito also shows how to leverage powerful Python-based machine learning tools in the .NET environment. Programming ML.NET will help you add machine learning and artificial intelligence to your tool belt, whether you have a background in these high-demand technologies or not.